Self-healing of Micro-cracks in Engineered Cementitious Composites - Benny Suryanto; S.A. Wilson; W.J. McCarter (Institute of Research and Community Outreach - Petra Christian University, 2015)
The performance of an Engineered Cementitious Composite (ECC) to self-heal micro-cracks under a controlled laboratory environment is presented. Ten dog-bone shaped samples were prepared; five of them were preloaded to known strains and then left to heal in water in a temperature-controlled laboratory. Ultrasonic pulse velocity (UPV) measurements were undertaken to monitor the crack-healing process. It was found that all samples exhibited recoveries in UPV and were able to recover to between 96.6% and 98% of their pre-test UPV values over a period of four weeks. An accelerated rate of healing was observed in the initial two-day period immediately following the preloading test.